PELATIHAN DIGITAL LEADERSHIP BAGI PERANGKAT DESA DI DESA PAMOKOLAN KECAMATAN CIHAURBEUTI KABUPATEN CIAMIS - Nursetiawan, Irfan; Yuliani, Dini; Taufiq, Otong Husni; Nurwanda, Asep; Anwar, Asep Nurdin Rosihan; Sujai, Ii; Firmanto, Candra (MALLOMO: Journal of Community Service, 2024)
This service activity is motivated by the lack of ability of the Village Government and Village Apparatus to lead and manage digital-based villages in Pamokolan Village. This activity includes Digital Leadership training in Pamokolan Village, Cihaurbeuti District, Ciamis Regency. This training is designed to equip village officials with the knowledge and skills needed in the digital era, including the use of information and communication technology (ICT) for administrative management, village community services, and data-based decision-making. The methods used in this training include lectures, discussions, and direct practice with digital devices. The participants were introduced to the basic concepts of digital leadership, digital applications that are relevant to village government, as well as strategies for implementing technology in daily website-based activities. The evaluation was carried out through a Focus Group Discussion with all Village Officials and the Head of Pamokolan Village. The results of this service activity show a significant increase in the understanding and ability of village officials to use digital technology and an increase in the Village Head's understanding of the importance of data. Participants can apply the knowledge gained to improve the efficiency and effectiveness of village operations and services to village communities. This training also strengthens village readiness in facing challenges and opportunities in the digital era, as well as improving the quality of public services to the community.